TajalliyÃ¢t Sufistik Dialektika Nilai-Nilai Religius-Humanistik - Hidayat, Husni (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
In Sufi dimension, a tarekat is considered a madrasa (school) which leads a mutasawwif to purify the darkness of heart from seven passions, namely ammârah bi al-sû?, lawwâmah, mulhamah, mutma?innah, râdiyah, and mardiyah. These seven lusts should be controlled and merged because they can cover humans from their nature. Under the guidance of the trustee murshid, the mutasawwifs are called and encouraged to reform their selves without seeing disgrace of other people. However, such process would not alienate the students from their social life and daily activities as the common people. Therefore, after two initial phases, namely takhallî and tahallî, a Sufi will reach his or her ultimate phase, i.e. tajallî. For the Sufis, the highest tajalli God is the Prophet. This is because he was the first creature of God and the most complete man (al-insân al-kâmil). Muhammad is not a mere man, but he is a manifestation of God?s emanation.